IFC in Nigeria : An Independent Country Impact Review - World Bank (Washington, DC, 2012)
Independent Evaluation Group's (IEG's) country impact review (the report) examines if, from July 1998 through December 2007, International Finance Corporation (IFC): (i) successfully defined a relevant and appropriate strategy for helping Nigeria tackle its most pressing needs; (ii) provided investment and advisory services that were reflective of IFC's strategy; and (iii) achieved positive development results. IFC's strategies in Nigeria reflected the characteristics of IFC's process for development of country strategies jointly with the World Bank. These characteristics include: (i) poor integration with IFC's main strategy and budget process; (ii) loosely formulated country objectives and priorities in terms of sectors and products; and (iii) little or no resource allocation. As a result, IFC's strategies for Nigeria have not fulfilled their purpose of setting priorities, defining targets, and securing the human, organizational, and other resources required.